Drinking from own cistern: customary institutions and their impacts on rural water management in Tanzania - Nkonya, Leticia Kuchibanda (Kansas State University, 2006)
Increasing human population, economic development and climatic changes in Sub-Saharan Africa have caused water scarcity, hence an urgent need for institutional arrangements that will lead to sustainable water management. This study analyzes the impact of customary institutions on rural water management in Tanzania, and shows how they might be used to complement the statutory institutions. The study was conducted in Bariadi district, northwestern Tanzania. The data were collected from household surveys, focus group discussions, key informants, participant observations, photographs, and secondary data sources. The results indicate that customary institutions are the most commonly used in regulating equitable access to water, prevention of water pollution and abuse, and natural resource conflict resolution. The awareness of the customary laws was higher than statutory laws because of the participatory nature of the customary institutions. Statutory institutions were found to be important for regulating water development issues. Villagers were not aware of statutory laws related to equitable water access, and prevention of water pollution and abuse. The study also found that customary institutions tend to discriminate against women. Women do not have land rights and were not allowed to participate in customary institutions activities. These results suggest the need for the government to recognize the importance of customary institutions in water management. The government needs to design policies and strategies that will ensure that women’s rights are respected by the customary institutions. There is also a need for fostering women’s participation in decision making, and designing cooperative institutions that are organized and governed by resource users themselves.
Keywords: Customary institutions; Statutory institutions; Water management; Tanzania; Sukuma; Bariadi; Sociology, General (0626)